7-phenoxytacrine is a dually acting drug with neuroprotective efficacy in vivo - Kaniakova, Martina; Korabecny, Jan; Holubova, Kristina; Kleteckova, Lenka; Chvojkova, Marketa; Hakenova, Kristina; Prchal, Lukas; Novak, Martin; Dolezal, Rafael; Hepnarova, Vendula; Svobodova, Barbora; Kucera, Tomas; et al. (Biochemical pharmacology, 2021)
N-methyl-D-aspartaterecepro receptor (NMDARs) are a subclass of glutamate receptors, which play an essential role in excitatory neurotransmission, but their excessive overactivation by glutamate leads to excitotoxicity. NMDARs are hence a valid pharmacological target for the treatment of neurodegenerative disorders; however, novel drugs targeting NMDARs are often associated with specific psychotic side effects and abuse potential. Motivated by currently available treatment against neurodegenerative diseases involving the inhibitors of acetylcholinesterase (AChE) and NMDARs, administered also in combination, we developed a dually-acting compound 7-phenoxytacrine (7-PhO-THA) and evaluated its neuropsychopharmacological and drug-like properties for potential therapeutic use. Indeed, we have confirmed the dual potency of 7-PhO-THA, i.e. potent and balanced inhibition of both AChE and NMDARs. We discovered that it selectively inhibits the GluN1/GluN2B subtype of NMDARs via an ifenprodil-binding site, in addition to its voltage-dependent inhibitory effect at both GluN1/GluN2A and GluN1/GluN2B subtypes of NMDARs. Furthermore, whereas NMDA-induced lesion of the dorsal hippocampus confirmed potent anti-excitotoxic and neuroprotective efficacy, behavioral observations showed also a cholinergic component manifesting mainly in decreased hyperlocomotion. From the point of view of behavioral side effects, 7-PhO-THA managed to avoid these, notably those analogous to symptoms of schizophrenia. Thus, CNS availability and the overall behavioral profile are promising for subsequent investigation of therapeutic use.
Keywords: Ion channel; Male; Behavioral experiment; neuroprotektivní látky; Rats, Wistar; HEK293 buňky; Electrophysiology; takrin; HEK293 Cells; Neuroprotective Agents; mužské pohlaví; potkani Wistar; krysa rodu Rattus; Hippocampus; Animals; lidé; Humans; zvířata; Rats; Mutation; Tacrine; Acetylcholinesterase; Receptors, N-Methyl-D-Aspartate; receptory N-methyl-D-aspartátu; hipokampus; Glutamate receptor